The effect of the exchange rate on inflation - an econometric study on the Algerian economy using the ARDL method for the period 1995-2021 - messeguem, noureddine; Chibout, slimane (Journal of Research in Finance and Accounting, 2023)
This study examines the relationship between the official exchange rate and the rate of inflation for the state of the Algerian economy during the period (1995-2021) using the quantitative approach represented by the Autoregressive Distributed Lagging Time Lag (ARDL) model, to reveal the existence of a long-term equilibrium relationship between the dependent variable and the explanatory variable. This standard study concluded that there is a long-term equilibrium relationship between the two variables, and that the official exchange rate has a negative impact on inflation in the short and long term.